The efficacy of first-trimester PAPP-A and free beta hCG levels for predicting adverse pregnancy outcome - (:unkn) unknown (WALTER DE GRUYTER GMBH, 2006)
Objective: To determine whether first-trimester measurements of maternal serum PAPP-A and free beta hCG levels were associated with adverse pregnancy outcomes. Study Design: First trimester maternal serum free bhCG and PAPP-A were measured in 490 singleton pregnancies. Pregnancies were followed by the fetal-maternal unit, and predictive efficacy of these markers for small for gestational age (SGA) babies, gestational diabetes mellitus and hypertensive disorders were analyzed by cut-off values determined by using a ROC analysis, and also, by using the fifth percentile as the cut-off value. Results: The sensitivities for PAPP-A in predicting pregnancies with a SGA baby and those complicated by a hypertensive disorder were 49% and 73%, respectively, when optimal cut-off values were used. Specificities were 76% and 65%, respectively. Serum free bhCG had no predictive value for individual pregnancy outcomes. Conclusion: Efficacy of first trimester maternal serum markers in predicting adverse pregnancy outcome is low. Even after optimization of cut-off values, these markers do not appear to be clinically acceptable as an effective tool for screening for adverse pregnancy outcomes.
Keywords: diabetes; hCG; PAPP-A; preeclampsia; pregnancy outcome; screening; SGA